Habilidades em comunicação na pediatria - Amaral, Anna Beatriz Costa Neves do (2012)
The quality of health communication is associated to better treatment adherence and greater degree of patient satisfaction. There are few studies on the assessment of the communication abilities of health professionals who assist children and adolescents. The Housestaff Communication Survey (HCS) is an instrument that evaluates the perception of the importance of 16 specific pediatric sills, the confidence for performing them and the institutional support offered. Objectives: Translate into Portuguese, culturally adapt it to Brazilian society and validate the Portuguese version of the HCS instrument, evaluate the importance of communication abilities, the confidence for communication and the institutional support offered to the respondents regarding their professional training and the development of communication abilities. Methods: The HCS questionnaire was translated into Portuguese, adapted culturally and its Portuguese version was validated, according to the guidelines recommended in the literature. The final Portuguese version was answered by medical students, pediatric residents and pediatricians of a university hospital. Face validity, internal consistency reliability, test-retest reproducibility and the missing data were assessed. Results: The final version was answered by 182 of the 200 eligible participants (response rate of 91%). The Cronbach's alpha reliability coefficient of the entire group was 0.929 for the scale of importance and 0.892 for the scale of confidence. The intraclass correlation coefficient was 0.796 for the scale of importance and 0.792 for the scale of confidence on test-retest. Twenty-five items were not answered (0.3%). Ninety-five percent of participants reported that effective communication with their patients is a priority and 94.5% indicated they had no previous participation in a program to improve their communication skills with patients. All the 16 items of the communication skills studied were rated as high or very high in importance. Concerning the scale of confidence, half or fewer of the participants indicated they felt rather or very confident about more advanced skills : speaking with children about serious illness, discuss end-of-life issues with patients and families, dealing with the difficult patient or parent, ability to respond to patients‟ emotions and giving bad news to patient and family. In the evaluation of the scales by subgroup, pediatricians were found to be more confident than students, and older respondents expressed greater confidence for performing the different communication items. The institutional support and incentives to the promotion of good physician-patient communication was found to be adequate for 62%. Conclusions: The translation in stages ensured an adequate Portuguese version both in the linguistic and technical aspects. The psychometric properties were adequate and similar to those in the original questionnaire. This instrument can be used for the assessment of the teaching of communication abilities in pediatrics and to identify the most difficult subjects that should be addressed as a priority in medical education.